An implementation study of the PDRD primary care computerized guidelines. - Jousimaa J; Kunnamo I; Mäkelä M (Scandinavian Journal of Primary Health Care)
OBJECTIVE: To study the implementation of electronic guidelines designed for general practitioners (GPs). DESIGN: A descriptive 3-year follow-up study. SUBJECTS: All new subscribers to Physician's Desk Reference and Database (PDRD) in 1992. SETTING: Locations of computers, where PDRD software was installed for the first time in 1992. MAIN OUTCOME MEASURES: Expectations of the program and changes in attitudes towards it, getting started with the system, frequency and continuity of use and estimated usefulness of the program. RESULTS: The guidelines were expected to enhance diagnostic accuracy (60% of subscribers), save time (45%), and reduce costs (11%). After 1 year's use, the opinions of the users on these topics had become slightly more positive. Technical problems delayed starting to use the program in 27%. After 1 year 72% were using the program at least weekly. Using frequency was associated with having the computer in the office. The subscribers who renewed their subscription after one year often became regular users. CONCLUSIONS: The study provides insight into the implementation phase of computer-based guidelines in a population of early adopters. Technical support was essential to overcome the barriers associated with computer technology. The perceived need for information was independent of the age and experience of the physicians.